High-level extracellular production of penicillin acylase by genetic engineering of Escherichia coli - Lin, W. J.; Huang, S. W.; Chou, C. P. (Journal of Chemical Technology and Biotechnology, 2001)
The extracellular production of penicillin acylase (PAC) in genetically engineered Escherichia coli by coexpression of the brp gene encoding bacteriocin release protein (BRP) and the pac gene was demonstrated. Cell physiology was affected while PAC was released into the medium, depending on the strategy for brp expression. The performance for the production and release of PAC was optimized by taking several culture parameters, including host, inducer (mitomycin C) concentration, and induction timing for brp expression, into consideration. The effect of PAC release on inclusion body formation was also investigated. It was observed that the amount of inclusion bodies was significantly affected by brp expression. A reason for the limitation of PAC production and a strategy for resolving this problem are proposed. (C) 2001 Society of Chemical Industry.